Comparison of the corrosion of materials in supercritical carbon dioxide, air, and argon environments. (November 2021) - Teeter, L.; Adam, B.; Wood, T.; Tucker, J.D.
Highlights: Mass gain per surface area and oxide thickness decreases with increasing material Ni and Cr content. The austenitic superalloys outperformed the ferritic martensitic steel and the austenitic stainless steel. Carbon dioxide and air exposures developed recrystallized zones under the oxide. Carbon dioxide exposures developed larger recrystallized zones than air. Recrystallization of the austenitic alloys appears to coincide with chromium depletion and oxide growth. Air exposures developed less uniform and thinner oxides. Abstract: The corrosion resistance of structural alloys was investigated in conditions that simulate supercritical carbon dioxide sCO 2 power fluid environments at 20 MPa and 550 ° C. Complementary air and Ar experiments were conducted at 1 atm. The alloys investigated in this study were as follows: Gr. 91, ferritic martensitic steel; 316L, austinetic stainless steel; HR 120, Ni-Fe based superalloy; and IN625, Ni based superalloy. The results for the air and sCO 2 exposed samples indicated parabolic mass-gain with respect to time and sCO 2 was more aggressive. The austinetic alloys exposed to sCO 2 developed recrystallized zones under the oxide. The same alloys exposed to air showed signs of recrystallization that was detectable with TEM.